104=-4(-4k-2)

Simple and best practice solution for 104=-4(-4k-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 104=-4(-4k-2) equation:



104=-4(-4k-2)
We move all terms to the left:
104-(-4(-4k-2))=0
We calculate terms in parentheses: -(-4(-4k-2)), so:
-4(-4k-2)
We multiply parentheses
16k+8
Back to the equation:
-(16k+8)
We get rid of parentheses
-16k-8+104=0
We add all the numbers together, and all the variables
-16k+96=0
We move all terms containing k to the left, all other terms to the right
-16k=-96
k=-96/-16
k=+6

See similar equations:

| ×-6y=-6-5×-7y=-7 | | 104=-4(-4k | | -104=-4(-4k-2 | | 3a+5=21 | | -4k+9=4 | | 96=4(4b-4 | | -60=-8n÷12 | | 0.3(c-5)=0.45(c+4) | | 0.3(12x-16=0.4(12x3) | | 29x-42=-132-x | | |4x−1|=|6x−4| | | 5b–28=27 | | q−11/2=4 | | q−112=4 | | 7.16x10^0= | | 5(4v+3)=-125 | | 4(4v+3)=-125 | | 3−(2t+5)=−12 | | 3−(2t+5)=−12= | | 3.99x10^1= | | -7(5-3x)-8x=-87 | | (1/3x)-4=(4/9x) | | -7(5-3x)-8=-87 | | -7(5-3x)-83=-87 | | -7(3-3x)-83=-87 | | 5(2-3m)=115 | | 23=x/3-11 | | 2÷x=0.2 | | X²+y²-32=0 | | –4d=–7d−6 | | -3(5t-3)+7t=2t-2 | | x=23-32+7 |

Equations solver categories